The Effect of Silybum marianum L. aquatic crude extracts on the cancer cell lines and normal cell line in vitro - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
The aquatic crude extract of Silybum marianum dry grains prepared by melting them in distil water by the method of soak and shake. The effect of Silybum marianum crude extract studied in vitro on three tumor cell line the Hep-2, AMN-3 and RD for 24, 48 and 72 hours of exposure, and one cell line of normal cells REF for 72 hr exposure. The results showed that the prescence of toxic effect of the aquatic crude extract on the cell lines of Hep-2, AMN-3 and RD at 10 and 100 µg/ ml upto the higher concentrations when they exposed to the extract for 48 hr. as compared with the control treatment, and when the exposure period increased to 72 hr. the toxic effect started at low concentrations (5 and 10 µg/ ml) as compared with the control group. Results comparision showed that the AMN-3 cell line was the most affected ane by the aquatic extract then the Hep-2 and RD, while normal REF was never affected. The microscopic test showed toxic effect for the low and high concentration of aquatic extract on the cells which was presented by obrious changes on the cell lines growth and loosing their distingwish cellular form.